Oil security revisited: An assessment based on complex network analysis. (1st March 2020) - Liu, Litao; Cao, Zhi; Liu, Xiaojie; Shi, Lei; Cheng, Shengkui; Liu, Gang
Abstract: Oil security has long been a political focus for the world major economies. However, existing literature on oil security assessment often omitted the network structure of the global oil trade, its dynamics, and individual countries' role in this complex network. In this paper, a hybrid assessment framework integrating complex network indicators of global oil trade with traditional indicators was established to assess oil security on both global and national levels from 1965 to 2016. We found the global oil trade has shown a pattern of diversified import sources and enhanced regional cooperation and there is a substantial decline in oil import dependence on the Middle East. The structure and features of global oil trade network imply both a small-world phenomenon and scale-free network characteristics. The value of the global oil security index has improved steadily, while most oil-importing countries show either an upward or relatively stable trend of oil security. Network structure factors such as average degree, edges, and transitivity on the global level, and degree and betweenness centrality on the national level deserve more attention. Our results from a complex network analysis perspective provide an improved understanding of oil trade and security as a whole in a globalizing era. Highlights: Gaps in the existing literature on oil security assessment are identified. Global and national oil security assessed based on complex network analysis. Trade patterns, network structure, and dynamics of the global oil trade revealed. Network structure factors become more important in ensuring oil security. Policies implied by an improved understanding of oil trade and security as a whole.